Pirate king : a novel of suspense featuring Mary Russell and Sherlock Holmes - King, Laurie R. (New York : Bantam Books, 2011)
Mary Russell, having been dispatched by Scotland Yard to investigate a silent film studio, goes undercover as part of a crew working on an adaptation of "The Pirates of Penzance" and realizes trouble is brewing when real pirates are hired as part of the cast and they begin to ignore the studio owner Randolph Fflytte's orders to follow their dangerous outlaw leader.
Booklist starred
Library Journal
Booklist starred, June 2011
Library Journal, June 2011
Adult
Adult
Keywords: Abduction -- Fiction; Holmes, Sherlock (Fictitious character) -- Fiction; Motion picture studios -- Fiction; Pirates -- Fiction; Russell, Mary (Fictitious character) -- Fiction; Women detectives -- England -- Fiction; Adventure fiction; Holmes, Sherlock (Fictional character) -- Fiction; Kidnapping -- Fiction; Motion picture studios -- Fiction; Mystery fiction; Pirates -- Fiction; Russell, Mary (Fictional character) -- Fiction; Women detectives -- Fiction; Mystery fiction; Suspense fiction